Manganese-Enhanced MRI: Biological Applications in Neuroscience - Malheiros, Jackeline Moraes; Paiva, Fernando Fernandes; Longo, Beatriz Monteiro; Hamani, Clement; Covolan, Luciene (Frontiers in Neurology, 2015)
Magnetic resonance imaging (MRI) is an excellent non-invasive tool to investigate biological systems. The administration of the paramagnetic divalent ion manganese (Mn2+) enhances MRI contrast in vivo. Due to similarities between Mn2+ and calcium (Ca2+), the premise of manganese-enhanced MRI (MEMRI) is that the former may enter neurons and other excitable cells through voltage gated Ca2+ channels. As such, MEMRI has been used to trace neuronal pathways, define morphological boundaries, and study connectivity in morphological and functional imaging studies. In this article, we provide a brief overview of MEMRI and discuss recently published data to illustrate the usefulness of this method, particularly in animal models.